Perbandingan Hukum Terkait Aborsi Hasil Pemerkosaan Menurut Hukum Islam dan Positif - H. B. Syafuri; Muhamad Wahyudin (Formosa Journal of Social Sciences (FJSS), 2022)
The case of pregnancy as a result of rape is very undesirable for all women who have a disease in society. The research method used is library research with qualitative research properties. The research approach uses a normative-juridical approach that refers to positive legal norms and Islamic law. The results of the research obtained in practice in Indonesia are reviewed from the perspective of positive law and Islamic law have in common, namely it is permissible for abortion to be provided with medical indications and both laws agree to prohibit abortion by individual means without the presence of medical personnel.